Learning while earning : the moderating role of gender in the relationship between work and common mental health symptoms. - Andri Eydal Þorvaldsson 1990-; Hilmar Lans 1991- (2022)
The purpose of this study was to explore the gender differences in anxiety and depression symptoms among university students in Iceland. The main objective was to evaluate if the amount of work parallel to studying was related to anxiety and depressive symptoms differently for male and female students. Researchers used Facebook to recruit participants and 375 Icelandic university students ranging from the age of 18-36 years old, and were they tasked with answering three Questionnaires; Generalized Anxiety Disorder Assessment, Patient Health Questionnaire 9 and Patient Health Questionnaire Anxiety-Depression Scale. The study revealed that the prevalence between gender of clinically relevant symptoms for anxiety among students, showed male students scored 23% overall and females 34% overall, but not showing statistical significance within different amounts of work. Clinically relevant symptoms for depression did not show statistically significant difference between gender, within the different amounts of work, but revealed that males scored 31,6% and females 36% overall. The study revealed that when testing the effects on gender and employment and their relationship with anxiety, depression or a combination of both, the results indicated a significant difference when it comes to gender within the anxiety group and in the combination group of depression but not within different amounts of work. Though there was only a statistical difference between gender but not for employment, there were interesting results displayed among women and men, regarding symptoms and amount of work showing a specific trend, where the least difference in symptoms between male and female students was among students working full time, but there was a noticeable increase in symptoms between men and women, when students were either working part time or non-working, especially for women.